Human Capital Development of Research Staff through Self-Leadership, Teamwork Management, and Culture Diversity - Jusriadi, Edi; Syafaruddin, Syafaruddin; Rusydi, Muhammad (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
Research related to the development of human capital based on cultural diversity is still minimal, so this study aims to find a human capital development model based on cultural diversity, self-leadership, and team management. The research instruments used questionnaires with samples of 146 respondents; the data was processed using SEM. The results showed that human capital performance could improve if supported by solid self-leadership despite cultural diversity. However, the research staff has not been able to do knowledge sharing because the management team has not entirely run well among local and foreign research staff. The novelty of this study lies in the ability to communicate between local and foreign research staff despite the cultural diversity between them.